Forecast of balance of a manpower as way of management of an environment of a youth segment of labor market - N. G. Vishnevskaya (Путеводитель предпринимателя, 2020)
In the article there researched problems of the management of youth labor-market segment conjuncture. The important part in this question is assigned to the working out labor resources-balance forecast. There considered main tendencies and perspectives of the development of regional youth labor-market segment. The author carried out the analyses of deficient and over professions on the basis of the amount of tension ratio on separate professions of workers and of fice employees.